O ensino de botânica na educação básica: dificuldades e o jogo como alternativa didática - Pereira, Jason Cardozo (Universidade Federal de São Carlos, 2021)
The teaching-learning process of botany has been frequently reported as difficult by students from the basic education and your teachers, who point out many factors as contributing to this didactic difficulty. The objective of this work was to raise the factors that negatively influence the teaching of Botany, through a survey of scientific articles published between 2018 and 2020. For this, we searched for works using the CAPES Portal and Scielo, which contained the expression “Teaching of Botany” in the title, as keywords and/or in the abstract. Sixteen works were found, from all regions of the country and related to basic education. After this survey, we observed that the massive amount of content, terms, concepts and processes, associated with the social effects of the phenomenon called “botanical blindness”, has contributed to the perpetuation of this problem. Along with this, the scarcity of proposals for alternative activities to traditional content classes proved to be one of the most present difficulties in the basic education network, aggravating this situation even more, causing students to distance themselves from botany, starting to observe it as something uninteresting and too complex. Among the alternative activities is the use of games in the classroom, with a didactic approach. This alternative is supported and recommended by Organs public bodies that govern education in our country, in addition, several studies point out the advantages of approaching certain contents in a playful way. With this in mind, we developed, as an alternative didactic proposal, a didactic game about plant reproduction to serve as support material for teachers in the basic education network. The game entitled “Musgolizando” brings elements for the teacher to work on concepts about plant reproduction, alternating generation, production and dispersion of spores, production and dispersion of gametes.
Botanical teaching in basic education: difficulties and a game as a didactic alternative
Keywords: Ensino de Botânica; Dificuldades de ensino; Jogo didático; Briófitas; Cegueira Botânica.; Botany Teaching; Teaching difficulties; Didactic game; Bryophytes; Plant blindness.; CIENCIAS HUMANAS::EDUCACAO